Meristic and morphometric identity of Baltic stocks of Atlantic salmon ( Salmo salar ) - MacCrimmon, Hugh R.; Claytor, Ross R. (Canadian Journal of Zoology, 1985)
Juvenile representatives of seven river stocks of Baltic salmon, Salmo salar, in northern, north-central, central, and southern Sweden are examined to determine if meristic and morphometric characters can be used to identify regional and home river origins. Morphometric features (> 80% accuracy) provide a better means of identification of salmon stocks than do meristic features. Both methods are congruent in identifying cohesive somatic salmon stocks based on river and regional geographic origin. Examination of within-stock differences between immature and mature (precocious) parr shows meristic homogeneity but significant morphological dichotomy. These significant morphological differences, involving different character sets, do not alter the capability to discern regional and river stocks containing disparate maturation stages of parr.